(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Globalization, the development of technology and the Internet make English the language of communication between different cultures and nations. English is one of the most popular and widespread languages in the world. It is not for nothing that knowledge of a foreign language is often found in the list of key skills in job descriptions. In this article, we will look at the issues related to the English language.